Mytilicola orientalis. Aquaculture International - Borkens, Y. & P. Koppe (30(4):1-9. Jul 2022, 2022)
Neozoa are invasive species that enter faunal communities as new species. Not infrequently, they pose a threat to local ecosystems. Climate change could further promote these developments or favor neozoa. Thus, they represent a relevant threat in the future. One of these neozoa is the copepod parasite Mytilicola orientalis. This parasite originates from Asia and infects a wide variety of bivalves like mussels and oysters. However, as an invasive species, it can be found more and more frequently in Europe, especially in the North and Baltic Seas. There, M. orientalis poses a real threat to mussels in aquaculture and thus also to the local economy.